Pre-Hospital Dietary Intake Correlates with Muscle Mass at the Time of Fracture in Older Hip-Fractured Patients - Calvani, Riccardo; Martone, Anna Maria; Marzetti, Emanuele; Onder, Graziano; Savera, Giulia; Lorenzi, Maria; Serafini, Elisabetta; Bernabei, Roberto; Landi, Francesco (Frontiers in Aging Neuroscience, 2014)
Background. Failure to meet an adequate dietary intake is involved in the pathogenesis of sarcopenia and osteoporosis, which in turn increase the risk for falls and fractures, respectively. Older people with hip fracture are often protein-malnourished at hospitalization. Whether low protein-energy intake is associated with muscle atrophy in hip fractured patients is presently unknown. This information is necessary for the development of novel strategies to manage this especially vulnerable patient population. The aim of this study was therefore to explore the relationship between dietary intake and muscle mass in older hip fractured patients. Methods. Analyses were conducted in hip fractured elderly admitted to an orthopedic and trauma surgery ward (University Hospital). Muscle mass was estimated by bioelectrical impedance analysis within 24 h from admission. Dietary information was collected via 24-h dietary recall and nutrient intakes calculated by a nutrition software. Results. Among 62 hip fractured patients (mean age 84.6±7.6 years, 84% women), the average energy intake was 929.2±170.3 Kcal/day, with higher values reported by men (1.046.8±231.4 Kcal/day) relative to women (906.5±148.3 Kcal/day; p=0.01). Absolute and normalized protein intake was 50.0±13.5 g/day and 0.88±0.27 g/kg (body weight)/day, respectively, with no gender differences. A positive correlation was determined between total energy intake and muscle mass (r=0.384; p=0.003). Similarly, protein and leucine consumption was positively correlated with muscle mass (r=0.367 and 0.311, respectively; p=0.005 for both). Conclusions. A low intake of calories, protein and leucine is associated with reduced muscle mass in hip fractured elderly. Given the relevance of sarcopenia as a risk factor for adverse outcomes in this patient population, our findings highlight the importance of a comprehensive dietary assessment for the detection of nutritional deficits predisposing to or aggravating muscle atrophy.